Skin Cancer in Childhood and Adolescents: Treatment and Implications for the Long-Term Follow-Up - Heinzerling, Lucie; Eigentler, Thomas Kurt (Springer International Publishing, 2020)
Skin cancer in childhood and adolescence is rare. Most young patients with cutaneous malignancies have underlying risk factors like a hereditary predisposition or immunosuppression. Rarely, patients present with spontaneous melanoma which can arise from congenital nevi. Treatment for skin cancer is being performed as in adults with the use of the paediatric support structures in addition to dermatooncological care. For medical therapies, e.g. systemic therapy of melanoma, basal or squamous cell carcinoma counselling on fertility has to be implemented as is standard for the younger adults. Since primary skin cancer is often associated with secondary skin cancers, patient education on preventive measures as well as regular clinical controls is crucial to ensure early detection.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Congenital; Excision; Fertility; Melanoma; Non-melanoma skin cancer; Squamous cell carcinoma